Odd Harmonious Labeling on Edge Amalgamation from Double Quadrilateral Graphs - Firmansah, Fery; Tasari, Tasari (Universitas Islam Negeri Raden Intan Lampung, 2020)
A graph that has odd harmonious labeling properties is called an odd harmonious graph. The purpose of this research is to obtain a new class graphs construction which is a family of odd harmonious graphs. The research method used consisted of several stages, namely research preparation, research investigation and verifivation of research results. The results of this study, we will give a line amalgamation construction of n double quadrilateral graphs DQ, denoted by *DQ(n) with n>= 1 and graph obtained by connecting between two graphs *DQ(n) with line graph L2, denoted by *(DQ(n),L2,DQ(n)). It has further been proven that *DQ(n) and *(DQ(n),L2,DQ(n)) have odd harmonious labeling properties, such that all of them are odd harmonious graphs.